Influence of the Xianshuihe Fault Zone on In-Situ Stress Field of a Deep Tunnel and its Engineering Effect - Yuan, Dong; Zhang, Lanbin; Liu, Xiaoling; Feng, Tao; Zhang, Guangze; Xu, Zhengxuan; Wang, Zhewei; Yi, Xiaojuan; Lin, Zhiheng; Ren, Yang; Zhang, Ru; Ren, Li (Frontiers in Earth Science, 2022)
The in-situ stress distribution near a fault zone is affected by factors such as tectonic movement and rock mass property deterioration, and it often shows unique characteristics and further affects the mechanical response of the rock mass and the safety of underground engineering construction. The Xianshuihe fault zone is one of the most active fault zones in the world. To understand the impact of the Xianshuihe fault zone on a tunnel under construction in southwestern China, the in-situ stress measured near the tunnel site at different distances from the faults of the Xianshuihe fault zone is obtained. Furthermore, the characteristics of the in-situ stress at the tunnel site and its engineering influence effect are analyzed. The results indicate the following: (1) Around the Xianshuihe fault zone, the fault mainly affects the maximum horizontal principal stress and the minimum horizontal principal stress in the shallow strata, and the in-situ stress closer to the fault is more greatly affected. (2) In the shallow area near the Selaha-Kangding fault, the maximum horizontal principal stress, minimum horizontal principal stress and lateral pressure coefficient at a borehole increase with increasing distance from the fault. Greater than 600 m from the fault, the horizontal stress plays a dominant role. In the deeper strata, the maximum horizontal principal stress, the minimum horizontal principal stress and the lateral pressure coefficient exhibit no obvious change with distance from the fault. (3) According to the inversion of the in-situ stress field and the stress in the tunnel site, the in-situ stress in the tunnel barrel is affected by the depth and the fault. The in-situ stress is higher at greater depths. The in-situ stress is partially released at the fault so that the in-situ stress is relatively low, and the degree of stress decline at different faults is different. (4) Tunnel rockbursts tend to occur in surrounding rock sections with high stress, which are usually located in the middle of a rock mass between two faults. Large deformation mainly occurs in the fault and its influence zone.